Relations Between Parents and Children in the Hadith of Imama Al-Bukhari - Narziyeva Xabiba (Zien Journals, 2022)
The article scientifically explores the ideas of goodness in the hadiths of Imam al-Bukhari and their significance today. The humanness of a person is determined primarily by his spiritual and moral perfection. Based on the foregoing, the main aspects of spiritual and moral improvement include: to consider it a duty of a person to please his parents, children, relatives, morals, character; respect for the cultural heritage left by our ancestors; respect and commitment to national values; stability of feelings of patriotism, nationalism, humanism; the tendency to be an example in relationships, to defend the Motherland, to be true to a promise, etc.
Keywords: perfect person; spiritually mature person; human duty; heritage of ancestors